2021
DOI: 10.3390/safety7040073
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Geometric Road Conditions on Safety Performance of Abu Dhabi Road Intersections

Abstract: Abu Dhabi’s government has taken several initiatives to improve the safety of the city’s highways, such as reducing traffic accident occurrence, red light violations, and property damage associated with traffic accidents. However, the intersections are still associated with many severe accidents, property damage associated with accidents, and red light violations. To help authorities pinpoint the major contributors to the deterioration of the safety performance of the signalized junctions, this study employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Alghafli et al [61] conducted a study with the aim of examining how conditions of geometric roads affect safety performance indicators, including severe accidents and property damage. The researchers utilized a negative binomial regression model in order to attain this objective.…”
Section: Road Geometric and Road Safetymentioning
confidence: 99%
See 2 more Smart Citations
“…Alghafli et al [61] conducted a study with the aim of examining how conditions of geometric roads affect safety performance indicators, including severe accidents and property damage. The researchers utilized a negative binomial regression model in order to attain this objective.…”
Section: Road Geometric and Road Safetymentioning
confidence: 99%
“…In Abu Dhabi, Alghafli at al. [61] carried out a study using a negative binomial regression model. The study aimed to identify the influence of geometric design conditions, such as the number of lanes in three-leg, four-leg, and other intersection types, on severe accidents, red light violations, safety performance indicators, and property damage.…”
Section: Road Geometric and Road Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…Traffic volume is the most commonly used independent variable for accident frequency modeling. Studies have shown that accidents increase with the increase in the annual average daily traffic (AADT) [19,32,34,35] or the average daily traffic (ADT) [36,37]. Conversely, Milton and Mannering [38] determined that an increase in traffic volume during peak hours reduces accident frequency (due to traffic congestion).…”
Section: Factors Affecting the Accident Frequencymentioning
confidence: 99%
“…The study also examines the relationship between horizontal curves on highways and road user safety and concludes that factors such as curve radius, superelevation, extra widening, and sight distance have a significant impact on road accidents. The study also looks at other factors such as traffic volume, geometric parameters of the curve, cross-section profile of the road, roadside hazards, visibility distance, curve direction, road friction, and traffic control devices, all of which had an importance on the safety performance at horizontal curves (Zhang, 2009;Islam et al, 2019;Alghafli et al, 2021). Generally, these road geometry factors affect the safety performance of highways (AlKheder et al, 2022).…”
Section: Introductionmentioning
confidence: 99%